The Effect of Online Learning on Student Motivation and Achievement during the Pandemic - Pratama, Nur Apna; Sari, Angereiny Citra; Batu Bara, Putri Khairul Nisa (Edumaniora : Jurnal Pendidikan dan Humaniora, 2024)
This study aims to analyze the impact of online learning on students' motivation and academic achievement during the COVID-19 pandemic. The method used in this study is a quantitative survey by distributing questionnaires to 300 high school students in various regions in Indonesia. The data obtained were analyzed using descriptive statistics and multiple regression analysis to identify the relationship between the variables studied. The results show that online learning has a significant effect on students' motivation to learn, with 65% of respondents reporting a decrease in motivation due to the challenges faced. However, the effect on academic achievement varied; students with good access to technology and strong family support showed a 20% increase in academic achievement compared to those with less support. Based on these findings, it is recommended that education policy prioritizes the development of more inclusive learning strategies, including improved access to technology and training for teachers in digital pedagogy, to ensure all students have equitable and quality learning opportunities.